The Effects of Risk and Credit Growth on the Stability of Regional Development Banks - Permata Eunike Roulina; Adam Zakaria; Muhammad Yusuf (Return : Study of Management, Economic and Bussines, 2026)
Bank stability plays a crucial role in maintaining financial cooperation functions and supporting regional financial systems resilience Regional Development Banks (RDBs) in Indicators serve as key institutions in regional financing economic activities. Therefore, their stability is closely related to risk management and credit intermediation performance. This study aims to examine the effect of liquidity risk, credit risk, operational risk, profitability risk, and credit growth on the stability of Regional Development Banks in Indicators Banking risks are proxied by Loan to Deposit Ratio (LDR), Non- Performing Loans (NPL), Operating Expenses to Operating Income (BOPO), and Net Interest Margin (NIM), when bank stability is measured using the Z- score indicator This study employs a quantitative approach with regional Development Banks as the unit of analysis over the 2020–2023 period Panel data analysis is applied to evaluate both partial and simultaneous effects of the independent variables on bank stability. Thie results indicates that banking risk varies affect bank stability differently NPL and BOPO negatively influence bank stability, while NIM has a positive and significant effect LDR, representing financial intermediation and credit growth activities contributions to bank stability within the simultaneous model Collectively LDR, NPL, BOPO, and NIM significantly influence the stability of Regional Development Banks. The findings highlight the importance of integrated risk management and balance credit expansion strategies to maintain sustainable stability in regional banking institutions